Cognitive Effects of PHT and CBZ After Brain Trauma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
The effects of prophylactic anticonvulsant use of phenytoin (PHT) and carbamazepine (CBZ) on the cognitive and emotional status of a total of 80 brain trauma patients are compared and reported from the Division of Neurosurgery and Department of Neurology, St Louis University School of Medicine and School of Public Health.